The impact of oil price regimes on construction costs in Nigeria - Olatunji, Oluwole (Rputledge, 2010)
Construction costs in Nigeria are often high and unpredictable. The pattern of variability is not explained byinflationary indices of common goods and services, but rather it is reactive to boom-and-burst shocks that aretriggered by oil price regimes. Pearson’s correlation analysis is deployed to examine the relationships betweenthe dynamics of crude oil price regimes (volume of crude oil export and price), selected indices ofmacrovariability—lending rate (prime), inflation rate and aggregate GDP growth, and supply deficit (demand–output gap) of local cement production. Analysis shows that construction cost is high because of high cost offinance and wild volatility that are stimulated by frictions in oil price regimes. Moreover, while the Nigerianconstruction industry shows positive growth and significant contribution to aggregate GDP growth in the pastdecade, the oil industry has persistently failed to trigger positive GDP growth. Furthermore, the variablesunder examination (as listed above) are also subjected to regression analysis to develop a mathematical modelfor predicting construction costs, relative to crude oil shock and defined macrovariability indices.Recommendations are made on how to avoid multicollinearity in similar studies and for areas of furtherstudies.